Optical laminate and image display device using same
By designing a specific uneven shape in the most surface -on -layer of optical layer, and calculating the average value of the power spectrum strength within the range of specific spatial frequency, the problem of being difficult to represent and designing optical layer fingerprint wipes in existing technology has achieved optics Features and fingerprint wiping effects.
Patent Information
- Application Number
- CN202380041416.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-18
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively represent and design the fingerprint wipeability of the optical laminated body for touch panel displays, especially since the roughness parameters cannot fully describe random and complex concave and convex shapes.
By designing a specific concave and convex shape on the outermost surface of the optical laminate and transforming it using three-dimensional data obtained by optical interference or contact measurement, the average value of the power spectrum intensity within a specific spatial frequency range is calculated to meet the specific A and B requirements. , C value range.
The realization of an optical laminate with excellent optical properties and fingerprint wipeability ensures high performance of the image display device and a good user experience.
Smart Images

Figure CN119365800A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical layered body and an image display device using the same. Background Art
[0002] AG (anti-glare) films have an anti-glare layer with fine concavo-convex shapes on the surface, and the fine concavo-convex shapes suppress the reflection of external light by diffusing reflected light. In addition, it is also known that a low refractive index layer (LR) is stacked on the anti-glare layer to further suppress reflected light by optical interference, and AGLR films are used in various displays.
[0003] The anti-glare properties of AG film and AGLR film are mainly determined by the surface roughness of the anti-glare layer. In the past, the preferred surface roughness of the anti-glare layer was often expressed using the surface roughness parameters specified in ISO 25178 and the line roughness parameters specified in JIS B 0601 (see, for example, Patent Documents 1 to 3).
[0004] Furthermore, AG films and AGLR films for displays with touch panels are required to have good wiping properties against fingerprints and the like that are attached during operation in addition to anti-glare properties.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5360616
[0008] Patent Document 2: Japanese Patent No. 5382034
[0009] Patent Document 3: Japanese Patent No. 6135131 Summary of the invention
[0010] Problems to be solved by the invention
[0011] The fingerprint wiping property required of an optical laminate for use in a display with a touch panel varies depending on the concavo-convex shape of the outermost surface. Therefore, as a method for expressing the fingerprint wiping property of an optical laminate, it is conceivable to use the above-mentioned roughness parameter and design an optical laminate with good fingerprint wiping property based on the roughness parameter.
[0012] However, the above-mentioned existing roughness parameters cannot represent all random concavoconvex shapes and complex concavoconvex shapes. For example, the arithmetic mean height Sa specified in ISO 25178 is an indicator commonly used to evaluate surface roughness, but even if the Sa value is the same, the concavoconvex shape and fingerprint wiping properties may be very different. Therefore, the previous roughness parameters are not suitable for representing fingerprint wiping properties.
[0013] An object of the present invention is to provide an optical laminate having excellent optical properties and fingerprint wiping properties, and an image display device using the same.
[0014] Means for Solving the Problem
[0015] The optical laminate of the present invention is characterized in that its outermost surface has an uneven shape and simultaneously satisfies the following conditions (1) to (3).
[0016] 40,000 ≤ A ≤ 300,000 (1)
[0017] 300 ≤ B ≤ 1,000 (2)
[0018] 30 ≤ C ≤ 500 (3)
[0019] Wherein, the three-dimensional data of the uneven height obtained by measuring the uneven shape by an optical interference method or a contact method is transformed into first image data with the uneven height as the pixel value, and the first image data is transformed into a second image by fast Fourier transform. When calculating the spatial frequency f of the X coordinate of the power spectrum of the image in the range of ±20 Pixel in the positive X-axis and Y-axis directions passing through the origin in the second image.
[0020] A: The average value of the power spectrum intensity in the range of 0 < f ≤ 100 cycle / mm.
[0021] B: The average value of the power spectrum intensity in the range of 100 cycle / mm < f ≤ 200 cycle / mm.
[0022] C: The average value of the power spectrum intensity in the range of 200 cycle / mm < f ≤ 300 cycle / mm.
[0023] The image display device of the present invention includes the above optical laminate.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide an optical laminate having excellent optical properties, appearance, and fingerprint wiping properties, and an image display device using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a cross-sectional view schematically showing an example of the optical laminate of the embodiment.
[0027] Figure 2 It is a cross-sectional view schematically showing another example of the optical laminate of the embodiment.
[0028] Figure 3 It is a diagram showing an evaluation method of antiglare property.
[0029] Figure 4 It is a figure which shows the evaluation example of anti-glare property. DETAILED DESCRIPTION
[0030] Figure 1 This is a cross-sectional view schematically showing an example of the optical layered body according to the embodiment.
[0031] The optical laminate 11 includes a transparent support 2 and an antiglare layer 3 (AG layer) laminated on one surface of the transparent support 2. The optical laminate 11 is an optical film (also referred to as an "AG film") that scatters incident light by fine irregularities on the outermost surface to suppress reflection of external light.
[0032] The transparent support 2 is a film that becomes the base of the optical laminate 11, and is formed of a material with excellent visible light transmittance. As the forming material of the transparent support 2, polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyacrylates such as polymethyl methacrylate; polyamides such as nylon 6 and nylon 66; transparent resins such as polyimide, polyarylate, polycarbonate, triacetyl cellulose, polyacrylate, polyvinyl alcohol, polyvinyl chloride, cycloolefin copolymer, norbornene-containing resin, polyether sulfone, and polysulfone, and inorganic glass can be used. The thickness of the transparent support 2 is not particularly limited, but is preferably set to 10 to 200 μm. In addition, when a low water vapor permeability is required, it is preferred to use a film composed of a material with a low water vapor permeability such as polyethylene terephthalate, cycloolefin polymer, and polypropylene.
[0033] In order to improve adhesion with other laminated layers, the surface of the transparent support 2 may be subjected to surface modification treatment. Examples of surface modification treatment include alkali treatment, corona treatment, plasma treatment, sputtering treatment, application of a surfactant or silane coupling agent, and Si vapor deposition.
[0034] The antiglare layer 3 is a functional layer that forms the fine concavo-convex shape of the outermost surface of the optical layered body 11 .
[0035] The antiglare layer 3 is formed by applying a coating liquid containing an active energy ray-curable compound and organic fine particles and / or inorganic fine particles (filler) on the transparent support 2 and curing the coating film.
[0036] As the active energy ray-curable compound, for example, a monofunctional, difunctional, or trifunctional or higher (meth)acrylate monomer can be used. In addition, in this specification, "(meth)acrylate" is a general term for both acrylate and methacrylate, and "(meth)acryloyl" is a general term for both acryloyl and methacryloyl.
[0037] Examples of the monofunctional (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, and tert-butyl (meth)acrylate. Isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphoric acid (meth)acrylate, ethylene oxide modified phosphoric acid (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified phenoxy (meth)acrylate meth)acrylate, nonylphenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiglycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acrylic acid adamantane derivative mono(meth)acrylates such as acryloyloxypropyl hydrophthalate, 2-(meth)acryloyloxypropyl hexahydrophthalate, 2-(meth)acryloyloxypropyl tetrahydrophthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, 2-adamantane, and adamantane acrylate having a monovalent mono(meth)acrylate derived from diamondoid, etc.
[0038] Examples of the bifunctional (meth)acrylate include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and hydroxyvaleric acid neopentyl glycol di(meth)acrylate.
[0039] Examples of trifunctional or higher-functional (meth)acrylates include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris-2-hydroxyethyl isocyanurate tri(meth)acrylate, glycerol tri(meth)acrylate and the like tri(meth)acrylates, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, di(trimethylol)propane tri(meth)acrylate and the like tri(meth)acrylates. Polyfunctional (meth)acrylate compounds having three or more functions, such as compounds, pentaerythritol tetra(meth)acrylate, di(trimethylol)propane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, di(trimethylol)propane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and di(trimethylol)propane hexa(meth)acrylate, and polyfunctional (meth)acrylate compounds in which a part of the above (meth)acrylates is substituted with an alkyl group or ε-caprolactone.
[0040] In addition, as a multifunctional monomer, urethane (meth)acrylate can also be used. As urethane (meth)acrylate, for example, there can be mentioned a product obtained by reacting an isocyanate monomer or prepolymer with a polyester polyol, and then reacting the obtained product with a (meth)acrylate monomer having a hydroxyl group.
[0041] Examples of urethane (meth)acrylates include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.
[0042] The above-mentioned multifunctional monomer may be used alone or in combination of two or more. The above-mentioned multifunctional monomer may be a monomer in the coating liquid or an oligomer obtained by partial polymerization.
[0043] Organic particles are materials that mainly form fine concavo-convex on the surface of the anti-glare layer 3 and impart the function of diffusing external light. As organic particles, resin particles formed by light-transmitting resin materials such as acrylic resin, polystyrene resin, styrene-(methyl)acrylate copolymer, polyethylene resin, epoxy resin, silicone resin, polyvinylidene fluoride, polyvinyl fluoride resin can be used. In order to adjust the dispersion of the refractive index and the resin particles, two or more resin particles with different materials (refractive index) can also be used in combination.
[0044] The inorganic fine particles added to the anti-glare layer-forming composition are preferably nanoparticles having an average particle diameter of 10 to 200 nm.
[0045] Inorganic particles are materials mainly used to adjust the sedimentation and aggregation of organic particles in the anti-glare layer 3. As inorganic particles, silica particles, metal oxide particles, various mineral particles, etc. can be used. As silica particles, for example, silica particles surface-modified with reactive functional groups such as colloidal silica or (meth) acryloyl groups can be used. As metal oxide particles, for example, aluminum oxide, zinc oxide, tin oxide, antimony oxide, indium oxide, titanium oxide, zirconium oxide, etc. can be used. As mineral particles, for example, mica, synthetic mica, vermiculite, montmorillonite, iron montmorillonite, bentonite, beidellite, soapstone, hectorite, sphenestone, nontronite, magadiite, green dapoxetine, hydromonite, layered titanic acid, montmorillonite, synthetic montmorillonite, etc. can be used. The mineral particles can be any one of natural and synthetic (including substitution bodies and derivatives), or a mixture of the two can be used. Among the mineral particles, layered organic clay is more preferred. Layered organic clay refers to a substance in which organic onium ions are introduced between the layers of swelling clay. There is no restriction on the organic onium ions as long as they can be organically formed by utilizing the cation exchangeability of swelling clay. As mineral particles, when using layered organic clay minerals, the above-mentioned synthetic montmorillonite can be preferably used. Synthetic montmorillonite has the function of increasing the viscosity of the anti-glare layer forming composition, inhibiting the sedimentation of resin particles and inorganic particles, and thus adjusting the concavo-convex shape of the surface of the optical functional layer.
[0046] In order to cure the anti-glare layer forming composition by ultraviolet irradiation, a polymerization initiator can be added. As a polymerization initiator, a polymerization initiator that generates free radicals by ultraviolet irradiation can be used. As a polymerization initiator, free radical polymerization initiators such as acetophenone, benzophenone, thioxanthone, benzoin, benzoin methyl ether, and acylphosphine oxide can be used. As a polymerization initiator, for example, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, bis (2,4,6-trimethylbenzoyl) phenyl phosphine oxide, 2,2-diethoxy acetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxyphenyl acetophenone, benzyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler's ketone, acetophenone, 2-chlorothioxanthone, etc. can be used. One of them can be used alone, or two or more can be used in combination.
[0047] In addition, in the anti-glare layer forming composition, as a component to improve antifouling properties, it is preferred to add an antifouling agent, a leveling agent, an oil repellent, a water repellent, and a fingerprint adhesion preventing agent. As the above-mentioned additives, it is preferred to use a fluorine-containing compound or a silicone compound. By adding an antifouling compound in the anti-glare layer 3 that becomes the outermost layer, the fingerprint wiping property can be further improved. In addition, various additives such as antistatic agents, defoamers, antioxidants, ultraviolet absorbers, infrared absorbers, colorants, light stabilizers, inhibitors, photosensitizers, antibacterial agents, antiviral agents, etc. can also be added as needed.
[0048] Furthermore, as required, a solvent may be added to the anti-glare layer forming composition. As the solvent, one or more of the following may be used: alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, isopropanol, and isobutanol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ketone alcohols such as diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, diethyl carbitol, and propylene glycol monomethyl ether; esters such as methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, and amyl acetate; ethers such as dimethyl ether and diethyl ether; N-methylpyrrolidone, dimethylformamide, and the like, or a mixture of two or more thereof.
[0049] Figure 2 This is a cross-sectional view schematically showing another example of the optical film according to the embodiment.
[0050] The optical laminate 12 includes a transparent support 2, an anti-glare layer 3 laminated on one surface of the transparent support 2, and a low refractive index layer 4 (LR layer) laminated on the surface of the anti-glare layer 3. The optical laminate 12 is an optical film (also called "AGLR film") that suppresses the reflection and reflection of external light by scattering and optical interference of incident light generated by fine concavoconvexities on the outermost surface.
[0051] The low refractive index layer 4 has a refractive index lower than that of the anti-glare layer 3 as the underlying layer, and is a functional layer for suppressing reflection by optical interference.
[0052] The low refractive index layer 4 can be formed by coating a composition containing an active energy ray-curable compound on the surface of the anti-glare layer 3 and curing the coating. The low refractive index layer 4 may contain low refractive index fine particles in order to adjust the refractive index.
[0053] As the low refractive index fine particles, for example, LiF, MgF, 3NaF·AlF or AlF (all with a refractive index of 1.4), or NaF can be preferably used. 3 AlF 6 (cryolith, refractive index 1.33) and other particles, silicon dioxide particles with voids inside. The silicon dioxide particles with voids inside are conducive to the low refractive index of the low refractive index layer 4 because the part of the void is set to the refractive index of air (about 1). Specifically, porous silicon dioxide particles and shell structured silicon dioxide particles can be used. In addition, low refractive index particles are not necessary. When the refractive index of the active energy ray-curable compound after curing is lower than the refractive index of the anti-glare layer 3, the low refractive index particles can also be omitted.
[0054] As the active energy ray-curable compound, the polymerizable compound described in the anti-glare layer can be used. In addition, the above-mentioned polymerization initiator or solvent can be appropriately added to the low refractive index layer forming composition.
[0055] Since low refractive index layer 4 is the functional layer that becomes the outermost layer, it is preferred to add antifouling agent, leveling agent, oil repellent, water repellent, fingerprint adhesion preventing agent as the component that improves antifouling property in the low refractive index layer forming composition. As the above-mentioned additive, fluorine-containing compound or silicone compound can be preferably used. In addition, various additives such as antistatic agent, defoamer, antioxidant, ultraviolet absorber, infrared absorber, colorant, light stabilizer, inhibitor, photosensitizer, antibacterial agent, antiviral agent etc. can also be added as required.
[0056] The above-mentioned antibacterial agent and antiviral agent may be a component that functions as either an antibacterial agent or an antiviral agent, or a component that functions as both an antibacterial agent and an antiviral agent, or a component that functions as an antibacterial agent or an antiviral agent depending on conditions such as the amount added.
[0057] The antibacterial agent and antiviral agent may be inorganic materials or organic materials. In addition, the antibacterial agent and antiviral agent may be in the form of particles or not. When the antibacterial agent and antiviral agent are in the form of particles, the average particle size is preferably 1 μm or less.
[0058] Functional components of inorganic materials that can be used as antibacterial agents and antiviral agents are, for example, metals such as silver, copper, zinc, metal oxides such as zinc oxide, and metal hydroxides such as calcium hydroxide. The above-mentioned metals can be metal particles, or can be in the form of ions, complexes, or salts. In addition, the above-mentioned metals can also be supported on a carrier. Carriers are, for example, phosphate-based carriers such as zeolite and zirconium phosphate, silica gel, activated carbon, glass materials, etc. In addition, the functional components of inorganic materials can also be compounds that act as photocatalysts such as titanium phosphate and photocatalysts such as titanium oxide. The above-mentioned compounds can also be used in combination with the above-mentioned metals. Among the above, as the functional components of inorganic materials, inorganic particles containing metals or metal oxides are preferably used, and materials containing silver are particularly preferably used.
[0059] Functional components of organic materials that can be used as antibacterial and antiviral agents may be synthetic or natural. Examples of synthetic components are quaternary ammonium salts, biguanide compounds such as polyhexamethylene biguanide, triclosan, etc. Examples of natural components are cypermethrin, terpenoids, etc.
[0060] Between the transparent support 2 and the anti-glare layer 3, one or more hard coating layers, high refractive index layers, medium refractive index layers, antistatic layers, electromagnetic wave blocking layers, infrared absorption layers, ultraviolet absorption layers, color correction layers and other functional layers may be stacked.
[0061] The coating method of the above-mentioned anti-glare layer forming composition and low refractive index layer forming composition is not particularly limited, and can be coated using, for example, a spin coater, a roll coater, a reverse roll coater, a gravure coater, a micro gravure coater, a knife coater, a rod coater, a wire rod coater, a die coater, a dip coater, a spray coater, an applicator, etc.
[0062] Here, the details of the surface irregularities of the optical layered body according to the present embodiment will be described.
[0063] The outermost surface irregularities of the optically functional laminate of the present embodiment satisfy the following conditions (1) to (3) at the same time.
[0064] 40,000≤A≤300,000 (1)
[0065] 300≤B≤1,000 (2)
[0066] 30≤C≤500 (3)
[0067] Among them, A, B and C are values derived from the spatial frequency f calculated from a specified range of the transformed image (power spectrum image) by fast Fourier transform (hereinafter referred to as "FFT") of image data generated from the measurement data of the concavo-convex height on the surface of the optical laminate. A is the average value of the power spectrum intensity in the range of 0<f≤100cycle / mm, B is the average value of the power spectrum intensity in the range of 100cycle / mm<f≤200cycle / mm, and C is the average value of the power spectrum intensity in the range of 200cycle / mm<f≤300cycle / mm.
[0068] The calculation method of the above-mentioned values of A, B and C is as follows.
[0069] First, three-dimensional data of the height of the concave and convex on the outermost surface of the optical laminate is obtained by measurement. The three-dimensional data of the height of the concave and convex includes the position within the measurement surface and the height of the concave and convex. The three-dimensional data of the height of the concave and convex on the outermost surface can be measured by optical interference or contact. The obtained three-dimensional data is transformed into an image (first image) with the height of the concave and convex as the pixel value. Then, FFT is performed on the first image to obtain an image after FFT processing (second image). Then, the X coordinate of the power spectrum of a specified range in the second image after FFT processing is transformed into a spatial frequency f. From the obtained spatial frequency, the real average value of the power spectrum intensity in the range of 0<f≤100cycle / mm, the range of 100cycle / mm<f≤200cycle / mm, and the range of 200cycle / mm<f≤300cycle / mm is calculated as the value of A, B and C mentioned above.
[0070] In the past, in order to make the fingerprint wipeability obvious, the outermost layer generally contains antifouling components such as fluorine compounds or silicone compounds, but the improvement of fingerprint wipeability is limited by simply adding antifouling components. After research, the inventors of the present application found that not only the material and components contained on the outermost surface, but also the surface concave-convex shape affect the fingerprint wipeability. In addition, after studying the concave-convex shape that can improve the fingerprint wipeability, the inventors of the present application found that the power spectrum intensity near the spatial frequency of 50cycle / mm has a great relationship with the fingerprint wipeability. The higher the power spectrum intensity near the spatial frequency of 50cycle / mm (that is, the higher the concave-convex height), the better the fingerprint wipeability.
[0071] When the above conditions (1) to (3) are met, the fingerprint wipeability is improved, which can be considered to be due to the combined effects of the oil repellent effect (Lotus effect) brought about by the unique surface concavoconvex shape and the surface concavoconvex shape being a shape that is easy to physically wipe. When any value of A to C is out of the range of conditions (1) to (3), the fingerprint wipeability is deteriorated, or the haze becomes higher due to enhanced surface scattering, or the appearance becomes white, etc., and the optical properties are deteriorated. In addition, mechanical properties such as scratch resistance may also deteriorate.
[0072] The optical laminates 11 and 12 of this embodiment have excellent fingerprint wiping properties because the outermost surface irregularities satisfy the above conditions (1) to (3). In addition, the fingerprint wiping properties can be further improved by adding an antifouling component such as an antifouling agent to the outermost functional layer.
[0073] The optical laminates 11 and 12 of this embodiment are used for the outermost surface of the device touched by fingers. Due to the social situation regarding the new coronavirus in recent years, the optical laminates 11 and 12 are also required to have antibacterial and antiviral properties. Therefore, by adding an antibacterial agent and / or an antiviral agent to the anti-glare layer 3 or the low refractive index layer 4, it can be made to have antibacterial and / or antiviral properties. If the antibacterial agent and / or antiviral agent is added to the outermost layer of the optical laminate, it is easy to obtain a higher antibacterial and / or antiviral effect, but even in the case where an antibacterial agent and / or an antiviral agent is added to the anti-glare layer 3 of a laminate such as the optical laminate 12, if the antibacterial component or the antiviral component is dissolved, the antibacterial and / or antiviral properties are exhibited.
[0074] The values of A to C can be controlled by adjusting the particle size or amount of the filler added to the anti-glare layer 3 , the amount of additives, the film thickness of the anti-glare layer 3 , and the aggregation state of the filler during the film forming process.
[0075] The optical laminates 11 and 12 of this embodiment can be attached to the outermost surface of an image display panel such as a liquid crystal panel or an organic EL panel to form an image display device. A touch panel can also be provided between the optical laminates 11 and 12 and the image display panel. The optical laminates 11 and 12 of this embodiment have excellent fingerprint wiping properties and are therefore suitable as optical films provided on the outermost surface of an image display device.
[0076] Example
[0077] Hereinafter, embodiments for implementing the present invention will be described.
[0078] (Example 1a)
[0079] The following hardcoat (HC) compositions were prepared.
[0080] (HC composition 1: for forming an anti-glare layer)
[0081] Organic fine particles having an average particle size of 3.5 μm (SSX-2035 manufactured by Techpolymer) were dispersed in toluene using a paint shaker for 40 minutes, and then 5.0 parts by mass of the organic fine particles, 92.0 parts by mass of a condensate of pentaerythritol and acrylic acid represented by the following formula (Viscoat #300 manufactured by Osaka Organic Chemical Industry Co., Ltd., hereinafter referred to as "PETA"), and 3.0 parts by mass of a photopolymerization initiator (Omnirad 184 manufactured by IGM Resins BV) were mixed into toluene. The total solid content concentration in the composition was adjusted to 50% by mass. The mixture was stirred for 40 minutes using a paint shaker to prepare HC composition 1.
[0082] [Chemistry 1]
[0083]
[0084] (HC composition 2: for forming a low refractive index layer)
[0085] 45.0 parts by mass of PETA (Viscoat #300 manufactured by Osaka Organic Chemical Industry Co., Ltd.), 50.0 parts by mass of isopropyl alcohol-dispersed hollow silica fine particles having an average particle size of 75 nm in terms of solid content, 3.0 parts by mass of a photoinitiator for UV curing photopolymerization initiator, and 2.0 parts by mass of a fluorine-based antifouling agent (KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd.) were added and mixed in isopropyl alcohol so that the total solid content concentration became 3.5% by mass, and the mixture was stirred for 40 minutes with a paint shaker to prepare HC composition 2.
[0086] Next, a 60 μm thick triacetyl cellulose (TAC) film (manufactured by Fujifilm, TJ40) was used as a transparent support. HC composition 1 was applied to one surface of the transparent support by a bar coater and dried at 100° C. for 1 minute in a dryer. A high-pressure mercury UV device was used in a nitrogen atmosphere (oxygen concentration was 500 ppm or less) so that the cumulative exposure amount reached 200 mJ / cm 2 The coating film was irradiated with ultraviolet rays in a manner to cure the coating film to form an anti-glare layer. In addition, the coating amount of the HC composition 1 was adjusted so that the film thickness after curing was 5 μm.
[0087] Next, HC composition 2 was applied on the antiglare layer using a bar coater and dried in a dryer at 100°C for 1 minute. A high-pressure mercury UV device was used in a nitrogen atmosphere (oxygen concentration was 500 ppm or less) to obtain a cumulative exposure of 200 mJ / cm 2The coating film was irradiated with ultraviolet rays in a manner to cure the coating film to form a low refractive index layer. In addition, the coating amount of the HC composition 2 was adjusted so that the optical film thickness nd (nd = refractive index n × film thickness d (nm)) after curing was 550 / 4nm.
[0088] (Example 2a)
[0089] An optical layered body was prepared in the same manner as in Example 1a, except that no fluorine-based antifouling agent was added to HC composition 2 and 47.0 parts by mass of PETA was blended.
[0090] (Example 3a)
[0091] An optical layered body was produced in the same manner as in Example 1a except that the amount of PETA in HC composition 1 was 90.0 parts by mass, 2.0 parts by mass of a fluorine-based antifouling agent (KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and no low refractive index layer was formed.
[0092] (Example 4a)
[0093] An optical layered body was produced in the same manner as in Example 1a except that the low refractive index layer was not formed.
[0094] (Example 5a)
[0095] An optical layered body was prepared in the same manner as in Example 1a, except that the dispersion time of the organic fine particles in HC composition 1 by the paint shaker and the stirring time of the coating liquid were both set to 60 minutes.
[0096] (Example 6a)
[0097] An optical layered body was prepared in the same manner as in Example 1a, except that the dispersion time of the organic fine particles in HC composition 1 by the paint shaker was changed to 60 minutes.
[0098] (Example 7a)
[0099] An optical layered body was prepared in the same manner as in Example 1a except that the organic fine particles in HC composition 1 were changed to organic fine particles having an average particle diameter of 3.0 μm (SSX-103 manufactured by Techpolymer).
[0100] (Example 8a)
[0101] An optical layered body was prepared in the same manner as in Example 7a, except that no fluorine-based antifouling agent was added to HC composition 2 and the blending amount of PETA was changed to 47.0 parts by mass.
[0102] (Example 9a)
[0103] An optical layered body was produced in the same manner as in Example 7a except that the amount of PETA in HC composition 1 was 90.0 parts by mass, 2.0 parts by mass of a fluorine-based antifouling agent (KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and no low refractive index layer was formed.
[0104] (Example 10a)
[0105] An optical layered body was produced in the same manner as in Example 7a except that the low refractive index layer was not formed.
[0106] (Example 11a)
[0107] An optical layered body was prepared in the same manner as in Example 1a except that the coating amount of the HC composition 1 was changed so that the film thickness after curing would be 6.0 μm.
[0108] (Example 12a)
[0109] An optical layered body was prepared in the same manner as in Example 11a, except that no fluorine-based antifouling agent was added to HC composition 2 and the blending amount of PETA was changed to 47.0 parts by mass.
[0110] (Example 13a)
[0111] An optical layered body was produced in the same manner as in Example 11a except that the amount of PETA in HC composition 1 was 90.0 parts by mass, 2.0 parts by mass of a fluorine-based antifouling agent (KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and no low refractive index layer was formed.
[0112] (Example 14a)
[0113] An optical layered body was produced in the same manner as in Example 11a except that the low refractive index layer was not formed.
[0114] (Example 1b-1)
[0115] An optical layered body was prepared in the same manner as in Example 1a except that 5.0 parts by mass of PETA in HC composition 1 was replaced with an antibacterial and antiviral agent (a silver-based antibacterial and antiviral agent (produced by Dainichi Seika: particles obtained by pulverizing PTC-NT (ST) with a bead mill and then subjecting it to dispersion treatment, average particle size: 0.5 μm).
[0116] (Example 1b-2)
[0117] An optical layered body was prepared in the same manner as in Example 1a except that 10.0 parts by weight of PETA in HC composition 1 was replaced with an antibacterial and antiviral agent (quaternary ammonium salt-based antibacterial and antiviral agent (manufactured by Kobayashi Pharmaceutical: KOBA-GUARD, non-particles)).
[0118] (Example 1c)
[0119] An optical layered body was prepared in the same manner as in Example 1a except that the transparent support in Example 1b-1 was replaced with a transparent support composed of a 75 μm-thick polyethylene terephthalate (PET) film (Lumirror #75-U34 manufactured by Toray).
[0120] (Examples 2b to 14b)
[0121] Optical layered bodies were prepared in the same manner as in Examples 2a to 14a except that 5.0 parts by mass of PETA in HC composition 1 was replaced with an antibacterial and antiviral agent (a silver-based antibacterial and antiviral agent (produced by Dainichi Seika: particles obtained by pulverizing PTC-NT (ST) with a bead mill and then subjecting it to a dispersion treatment, average particle size: 0.5 μm).
[0122] (Comparative Example 1)
[0123] An optical layered body was prepared in the same manner as in Example 1a except that the coating amount of the HC composition 1 was changed so that the film thickness after curing would be 4.0 μm.
[0124] (Comparative Example 2)
[0125] An optical layered body was prepared in the same manner as in Example 1a except that the coating amount of the HC composition 1 was changed so that the film thickness after curing would be 7.0 μm.
[0126] (Comparative Example 3)
[0127] An optical layered body was prepared in the same manner as in Example 1a except that the organic fine particles in HC composition 1 were changed to organic fine particles having an average particle diameter of 5.0 μm (manufactured by Techpolymer, SSX-105).
[0128] (Comparative Example 4)
[0129] An optical layered body was prepared in the same manner as in Example 1a except that the organic fine particles in HC composition 1 were changed to organic fine particles having an average particle diameter of 2.5 μm (SSX-102 manufactured by Techpolymer).
[0130] (Comparative Example 5)
[0131] An optical layered body was prepared in the same manner as in Example 1a except that the blending amount of PETA in HC composition 1 was 90.0 parts by mass and the blending amount of organic fine particles (SSX-2035 manufactured by Techpolymer) was 7.0 parts by mass.
[0132] (Comparative Example 6)
[0133] An optical layered body was produced in the same manner as in Example 1a except that the blending amount of PETA in HC composition 1 was 94.0 parts by mass and the blending amount of organic fine particles was 3.0 parts by mass.
[0134] (Comparative Example 7)
[0135] An optical layered body was prepared in the same manner as in Example 1a, except that the dispersion time of the organic fine particles in HC composition 1 by the paint shaker was changed to 20 minutes.
[0136] (Comparative Example 8)
[0137] An optical layered body was prepared in the same manner as in Comparative Example 7 except that no fluorine-based antifouling agent was added to HC composition 2 and the blending amount of PETA was changed to 47.0 parts by mass.
[0138] (Comparative Example 9)
[0139] An optical layered body was produced in the same manner as in Comparative Example 7 except that the amount of PETA in HC composition 1 was 90.0 parts by mass, 2.0 parts by mass of a fluorine-based antifouling agent (KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and no low refractive index layer was formed.
[0140] (Comparative Example 10)
[0141] An optical layered body was produced in the same manner as in Comparative Example 7 except that the low refractive index layer was not formed.
[0142] (Comparative Example 11)
[0143] An optical layered body was prepared in the same manner as in Example 1a, except that the dispersion time of the organic fine particles in HC composition 1 by the paint shaker and the stirring time of the coating liquid were changed to 80 minutes.
[0144] (Comparative Example 12)
[0145] An optical layered body was prepared in the same manner as in Comparative Example 11 except that no fluorine-based antifouling agent was added to HC composition 2 and the blending amount of PETA was changed to 47.0 parts by mass.
[0146] (Comparative Example 13)
[0147] An optical layered body was produced in the same manner as in Comparative Example 11 except that the amount of PETA in HC composition 1 was 90.0 parts by mass, 2.0 parts by mass of a fluorine-based antifouling agent (KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and no low refractive index layer was formed.
[0148] (Comparative Example 14)
[0149] An optical layered body was produced in the same manner as in Comparative Example 11 except that the low refractive index layer was not formed.
[0150] The optical layered bodies of the respective Examples and Comparative Examples were evaluated as follows.
[0151] <Evaluation 1: Surface irregularities>
[0152] (Acquisition of three-dimensional data)
[0153] The three-dimensional data of the concavo-convex shape of the outermost surface of the optical laminate was measured by optical interference using Vertscan (Ryoka Systems, R3300H Lite). The measurement conditions were as follows: The concavo-convex height was based on the lowest position in the measurement range.
[0154] Camera model: Sony HR-50 1 / 3
[0155] Objective lens magnification: 5XTI
[0156] ·Eyepiece: 1X
[0157] Zoom lens: 1X
[0158] Light source: 530white
[0159] Wavelength filter: 520nm
[0160] ·Measurement equipment: Piezoelectric
[0161] ·Measurement mode: Phase
[0162] Scanning speed: 4μm / sec
[0163] Scanning range: 10μm~-10μm
[0164] · Number of effective pixels: 0%
[0165] · Measurement range: 940.8μm×705.6μm, 640pixel×480pixel
[0166] XY resolution: 1 pixel 1.47 μm
[0167] (FFT analysis)
[0168] FFT analysis was performed using the free software "ImageJ 1.53h" under Windows (registered trademark) 10. The steps are as follows.
[0169] 1. Convert the 3D data into TIFF image data with height as pixel value.
[0170] 2. Perform FFT with reference to the original three-dimensional data value (measured value of height). The image size after FFT processing is set to 1024 pixels × 1024 pixels.
[0171] 3. The power spectrum intensity of the image after FFT processing was restored to the actual measured value.
[0172] 4. In the processed image, specify the range of ±20 pixels on the positive X-axis passing through the origin, and output the power spectrum intensity.
[0173] 5. Transform the X coordinate of the output power spectrum into the spatial frequency f according to the pixel size of the original three-dimensional data.
[0174] 6. Based on the calculated spatial frequency, calculate the true average value (values of A to C) of the power spectrum intensity in each range of 0<f≤100cycle / mm, 100cycle / mm<f≤200cycle / mm, and 200cycle / mm<f≤300cycle / mm.
[0175] <Evaluation 2: Optical properties>
[0176] The optical properties of the optical layered body were evaluated based on the following evaluations of haze, anti-glare properties, and reflectivity, and were evaluated according to the following criteria.
[0177] ◎: In the evaluation of haze, anti-glare property, and reflectivity, one or more of them are evaluated as ◎, and the rest are evaluated as ○
[0178] ○: Haze, anti-glare properties, and reflectivity were all evaluated as ○
[0179] ×: Haze, anti-glare, reflectivity have more than one evaluation ×
[0180] (Haze)
[0181] The haze was measured using a haze meter (NDH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with the haze test method of optical properties test method for plastics JIS K 7136. The evaluation criteria for optical properties are as follows.
[0182] ◎: Haze is 6% or more and less than 8%
[0183] ○: Haze is 4% or more and less than 6%, or 8% or more and less than 10%
[0184] ×: Haze is less than 4% or more than 10%
[0185] (Anti-glare)
[0186] Figure 3 is a diagram showing the evaluation method of anti-glare properties, Figure 4It is a figure which shows the evaluation example of anti-glare property.
[0187] The obtained optical laminate was bonded to a blackboard using an optical adhesive in such a manner that the functional surface was the surface. In addition, a three-wavelength fluorescent lamp and an optical laminate were arranged in such a manner that light was irradiated perpendicularly to the functional surface. The surface of the optical laminate was observed from a direction at 70° relative to a perpendicular line from the three-wavelength fluorescent lamp to the functional surface, where a line connecting the viewpoint and the image of the three-wavelength fluorescent lamp projected on the functional surface was observed, and the anti-glare property was evaluated according to the following criteria.
[0188] 0: The outline of the three-wavelength fluorescent lamp can be seen, but the edges are blurred.
[0189] ×: The outline of the three-wavelength fluorescent lamp is too blurry to be seen, or the edge is clearly visible
[0190] (Reflectivity)
[0191] The spectral reflectance of the functional layer surface of the obtained optical laminate at an incident angle of 5° was measured using an automatic spectrophotometer (U-4100, manufactured by Hitachi, Ltd.) and evaluated according to the following criteria. During the measurement, a matte black coating was applied to the back side of the TAC film (the side without the functional layer formed) to perform an anti-reflection treatment.
[0192] ◎:Reflectivity less than 0.5%
[0193] ○: Reflectivity is 0.5% or more and less than 1%
[0194] ×: Reflectivity is 1% or more
[0195] <Evaluation 3: Fingerprint Wiping Properties>
[0196] The obtained optical laminate was bonded to a blackboard using an optical adhesive so that the functional surface was the surface. The artificial leather with the olive oil reagent attached was pressed on the functional surface to attach the olive oil, and the attached olive oil was repeatedly wiped with a paper towel (Scotty (registered trademark), manufactured by Nippon Paper Kracie Co., Ltd.) at a load of 1 kg. Each time the olive oil was wiped, the reflected light spectrum of the olive oil attachment was measured using a spectrophotometer (CM-2500d, manufactured by Konica Minolta). The measurement conditions are as follows.
[0197] ·Measurement diameter: Φ8mm
[0198] Project: SCI / SCE
[0199] Light source: D65
[0200] UV setting: 100%
[0201] Observation field: 10°
[0202] The color difference ΔE*ab before and after the olive oil was applied was calculated, and the number of wiping when the color difference ΔE*ab reached 0.5 or less was used as the evaluation value. Evaluation was performed according to the following criteria.
[0203] ◎: Wipe times less than 5 times (fingerprint wipeability is very good)
[0204] ○: The number of wipes is 5 or more and less than 10 times (good fingerprint wipeability)
[0205] △: Wipe times more than 10 times and less than 30 times (fingerprints are difficult to wipe off)
[0206] ×: Wipe more than 30 times (fingerprints are very difficult to wipe off or cannot be wiped off)
[0207] <Evaluation 4: Antibacterial property>
[0208] The functional surface of the optical laminate was subjected to an antibacterial test against Escherichia coli and Staphylococcus aureus in accordance with JIS Z 2801. A polyethylene film was used as an unprocessed sample and the evaluation was performed according to the following criteria.
[0209] ○: The antibacterial activity values of both Escherichia coli and Staphylococcus aureus are 2.0 or more
[0210] ×: The antibacterial activity value of at least one of Escherichia coli and Staphylococcus aureus is less than 2.0
[0211] <Evaluation 5: Antiviral properties>
[0212] The functional surface of the optical laminate was subjected to an antiviral test against influenza A virus and feline calicivirus in accordance with ISO 21702. A polyethylene film was used as an unprocessed sample and the evaluation was performed according to the following criteria.
[0213] ○: The antiviral activity value of at least one of influenza A virus and feline calicivirus is 2.0 or more
[0214] ×: The antiviral activity values of influenza A virus and feline calicivirus are both less than 2.0
[0215] <Evaluation 6: Scratch resistance>
[0216] The obtained optical laminate was placed on a Gakushin type friction fastness tester (AB-301, manufactured by Tester Industry Co., Ltd.) and steel wool (Bonstar #0000) was rubbed at 500 g / cm 2 The surface of the optical layered body was contacted with a pressure of 10000 and a scratch resistance test was performed by reciprocating 10 times. After the scratch resistance test, the surface of the optical layered body was visually observed and evaluated according to the following criteria.
[0217] 0: No scratches
[0218] ×: There is one or more scratches
[0219] <Evaluation 7: Water Vapor Transmission Rate>
[0220] The moisture permeability of the obtained optical film and the moisture permeability of the transparent substrate were measured at 40°C and 90 RH% according to the moisture permeability test method (cup method) for moisture-proof packaging materials specified in JIS Z 0208:1976, and evaluated according to the following criteria.
[0221] ○: Moisture permeability is 150g / (m 2 ·day) or less
[0222] ×: Moisture permeability value exceeds 150g / (m 2 ·day)
[0223] Tables 1 to 3 show the evaluation results.
[0224]
[0225]
[0226]
[0227] As shown in Table 1, in the optical laminates of Examples 1a to 14a, A to C satisfy conditions (1) to (3), and both the optical properties and fingerprint wiping properties are excellent, and the scratch resistance is also good. Even when no antifouling agent is added to the outermost functional layer, the fingerprint wiping property is good, but by adding an antifouling agent to the outermost functional layer, the fingerprint wiping property becomes very good. In addition, the optical laminates of Examples 1b-1, 1b-2, 1c, 2b to 14b also satisfy conditions (1) to (3), and the optical properties, fingerprint wiping properties and scratch resistance are excellent. In addition, the optical laminates of Examples 1b-1, 1b-2, 1c, 2b to 14b have both antibacterial and antiviral properties because the anti-glare layer contains an antibacterial and antiviral agent. The optical laminate of Example 1c uses a low moisture permeability PET film as a transparent support, so the water vapor permeability is reduced.
[0228] On the other hand, in the optical layered bodies of Comparative Examples 1 to 14, at least one of A to C did not satisfy the above conditions, and one or both of the optical characteristics and the fingerprint wiping property were evaluated low.
[0229] From the above, it was confirmed that an optical layered body having excellent optical properties and fingerprint wiping properties can be realized by making the above A to C satisfy the conditions (1) to (3) simultaneously.
[0230] Industrial Applicability
[0231] The present invention can be used as an optical film provided on the outermost surface of an image display device.
[0232] Explanation of symbols
[0233] 1. Optical laminate
[0234] 2Transparent support
[0235] 3 Anti-glare layer
[0236] 4 Low refractive index layer
Claims
1. An optical laminate, characterized in that: The optical layered body has a concavoconvex shape on the outermost surface and satisfies the following conditions (1) to (3) at the same time. 40,000≤A≤300,000 (1) 300≤B≤1,000 (2) 30≤C≤500 (3) In which, the three-dimensional data of the concavo-convex height obtained by measuring the concavo-convex shape by an optical interference method or a contact method is transformed into the first image data with the concavo-convex height as a pixel value, and the first image data is transformed into the second image by fast Fourier transform, and the spatial frequency f of the X coordinate of the power spectrum of the image in the second image passing through the origin and in the range of ±20 pixels on the positive X axis and the Y axis direction is calculated, A: The average value of the power spectrum intensity in the range of 0<f≤100cycle / mm, B: The average value of the power spectrum intensity in the range of 100cycle / mm<f≤200cycle / mm, C: Average value of the power spectrum intensity in the range of 200 cycle / mm<f≤300 cycle / mm.
2. The optical layered body according to claim 1, wherein: The optical layered body includes a transparent support and a first functional layer laminated on at least one surface of the transparent support, wherein the concavo-convex shape of the outermost surface is formed by the first functional layer.
3. The optical laminate according to claim 2, wherein: A second functional layer having a refractive index lower than that of the first functional layer is provided on the first functional layer.
4. The optical layered body according to claim 2, wherein: The first functional layer contains an antifouling agent.
5. The optical layered body according to claim 3, characterized in that: The second functional layer contains an antifouling agent.
6. The optical layered body according to claim 2, characterized in that: The first functional layer contains a fluorine-containing compound or a silicone compound.
7. The optical layered body according to claim 3, characterized in that: The second functional layer contains a fluorine-containing compound or a silicone compound.
8. The optical layered body according to claim 2, wherein: The first functional layer contains an antibacterial agent and / or an antiviral agent.
9. The optical layered body according to claim 3, characterized in that: The first functional layer or the second functional layer contains an antibacterial agent and / or an antiviral agent.
10. The optical layered body according to claim 2, wherein: The transparent support is formed of a material with low moisture permeability. 11 . An image display device comprising the optical layered body according to claim 1 .
Citation Information
Patent Citations
Differential type magnetic head
JP1978060616A
Automatic water gate
JP1978082034A
Rotor unit
JP1986035131A